Phi Beta Kappa records - Phi Beta Kappa
Correspondence, minutes, reports, financial records, publications, printed matter, and other records relating to the functions of the organization. Includes material pertaining to the evaluation of institutions applying for local chapters and book awards granted annually by Phi Beta Kappa. Subjects include the American Scholar, the Key Reporter, liberal arts studies, collegiate athletics, history of Phi Beta Kappa, and role of honor societies in education. Individuals represented include Carl Billman, Christian Frederick Gauss, Edwin A. Grosvenor, William T. Hastings, Benno Lewinson, Marjorie Hope Nicholson, Clark Sutherland Northrup, William A. Shimer, Charles Franklin Thwing, and Oscar M. Voorhees. Includes correspondence with organizations such as the American Association for the Advancement of Science and the National Humanities Faculty.
Collegiate scholastic honor society founded in 1776 at the College of William and Mary, Williamsburg, Va.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Billman, Carl; Gauss, Christian Frederick, -- 1878-1951.; Grosvenor, Edwin A. -- 1845-1936.; Hastings, William T. -- 1881-1969.; Lewinson, Benno; Nicholson, Marjorie Hope; Northrup, Clark Sutherland, -- 1872-1952.; Shimer, William A. -- 1894-; Thwing, Charles Franklin, -- 1853-1937.; Voorhees, Oscar M. -- 1864-1947.; American Association for the Advancement of Science; National Humanities Faculty; College sports; Education, Humanistic; Learned institutions and societies; Literary prizes; Universities and colleges; American scholar; Key reporter